Reformulation of Agrarian Regulations Within a Human Rights Framework - Agus Suntoro; Nurrahman Aji Utomo; Mardhika Agestyaning Hermanto (University of Jember, 2022)
The complexities of land and natural resource cases involve multiple stakeholders ranging from the government and security forces to corporations. The conflicts that drive these cases are reflected in the Indonesian Commission on Human Rights data and in complaints from civil society. One contributing issue is driven by regulatory factors in the agrarian sector that is not in line with international human rights principles and norms. The analysis of these problems will be described in three discussions: one identifying the meaning of agrarian followed by a model for internalizing human rights instruments and principles in domestic regulations, and one affirming the responsibilities of the State and of corporations in the business. This paper concludes that differences in agrarian terms in various laws cause problems in norms and practices that affect multiple conflicts. Second, it emphasizes the urgency with which key players must evaluate different sectoral rules related to land and natural resources as well as harmonize domestic regulations with human rights principles and norms; and third, it underscores the importance of strengthening the responsibility of the State in regulating corporations to respect human rights and to make remedies for victims. Keywords: land and natural resources, agrarian reform, human rights instruments and principles, state and corporate responsibility